Therapeutic alliance, empathy, and genuineness in individual adult psychotherapy: A meta-analytic review - Nienhuis, Jacob B.; Owen, Jesse; Valentine, Jeffrey C.; Winkeljohn Black, Stephanie; Halford, Tyler C.; Parazak, Stephanie E.; Budge, Stephanie; Hilsenroth, Mark (Psychotherapy research, 2018)
Objective: Alliance, empathy, and genuineness are each integral parts of the therapeutic relationship. No previous meta-analysis has explored the extent to which therapist empathy and genuineness contribute to the therapeutic alliance. Method: In this meta-analysis, a multifaceted search strategy yielded 53 studies. Forty studies reported alliance/empathy relationships, eight studies reported alliance/genuineness relationships, and five studies reported both. Results: Random effects meta-analyses revealed that therapeutic alliance was significantly related to perceptions of therapist empathy with a mean r = 0.50 (95% CI = 0.42, 0.57). Therapeutic alliance was also significantly related to perceptions of therapist genuineness with a mean r = 0.59 (95% CI = 0.45, 0.71). Tests of publication bias indicated a low likelihood of publication bias affecting the strength and direction of the results. Potential moderating variables were explored, including rater perspective, measure of therapeutic relationship variables, and client race/ethnicity. Conclusions: Therapeutic alliance has a moderate relationship with perceptions of therapist empathy and genuineness. Of note, there may be reason to believe that when rated by the same person, these constructs have significant overlap and lack discreteness. Future directions for study of the therapeutic relationship are discussed. Implications for practice are provided.